1999
DOI: 10.1038/sj.leu.2401254
|View full text |Cite
|
Sign up to set email alerts
|

Outcome for children with relapsed acute myeloid leukaemia following initial therapy in the Medical Research Council (MRC) AML 10 trial

Abstract: children with acute myeloid leukaemia (AML) were treated in the MRC AML 10 trial. Three risk groups were identified based on cytogenetics and response to treatment. One hundred and twenty-five children relapsed -103 in the bone marrow only, 12 in the bone marrow combined with other sites, and six had isolated extramedullary relapses (site was not known in four cases). Eighty-seven children received further combination chemotherapy, one all-trans retinoic acid for acute promyelocytic leukaemia, and one a matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
100
3
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 15 publications
18
100
3
6
Order By: Relevance
“…Comparable observations have been reported by other groups: A 3-year OS rate of 24% after relapse was reported for treated and untreated pediatric patients from the MRC (Medical Research Council) AML10 trial. 6 The 5-year OS was 34% in 146 patients from the NOPHO (Nordic Society for Pediatric Hematology and Oncology) studies 9 and 33% in 106 patients treated within the French LAME (Leucémie Aiguë Myéloblas-tique Enfant) 89/91 protocol. 3 Data from the St Jude institutional trials showed a 5-year OS of 23% in 160 relapse patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable observations have been reported by other groups: A 3-year OS rate of 24% after relapse was reported for treated and untreated pediatric patients from the MRC (Medical Research Council) AML10 trial. 6 The 5-year OS was 34% in 146 patients from the NOPHO (Nordic Society for Pediatric Hematology and Oncology) studies 9 and 33% in 106 patients treated within the French LAME (Leucémie Aiguë Myéloblas-tique Enfant) 89/91 protocol. 3 Data from the St Jude institutional trials showed a 5-year OS of 23% in 160 relapse patients.…”
Section: Discussionmentioning
confidence: 99%
“…Survival after recurrence was poor so far, ranging from 21 to 33%. [3][4][5][6] The duration of first complete remission (CR1) has been reported to be the major prognostic factor in relapse with a 5-year survival of only 10% in early relapse defined as relapse occurring within 12 months after diagnosis. 5 French-American-British (FAB) subtypes as well as cytogenetics and intensity of first-line treatment including allogeneic stem cell transplantation (allo-SCT) are well recognized as additional prognostic factors in the relapse setting.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] To improve the treatment outcome of these patients; high-dose chemo/ radiotherapy combined with allogeneic HSCT has been undertaken. Data from series of children transplanted for AML in CR2 are limited.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although CR2 may be achieved in the majority of these children with chemotherapy alone, long-term survival is limited to 8-33%. [4][5][6] While most would recommend allogeneic hematopoietic stem cell transplant (HSCT) as therapy for relapsed AML, the role of HSCT is less certain for children with AML in CR1. 1,2,7 With the excellent results of chemotherapy and the known risks and long-term side effects of HSCT, the decision to proceed with HSCT in CR1 remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an initial complete remission rate of 90%, 30% to 40% of the pediatric patients with AML relapse, and the 5-year overall survival rate is approximately 60% (1)(2)(3). Therefore, certain leukemic cells have to be resistant to current treatment strategies, and persist after therapy.…”
Section: Introductionmentioning
confidence: 99%